Electrolytes containing lithium difluoro(oxalato)borate and lithium tetrafluoroborate salts for lithium metal and anode-free batteries

By using a double-salt electrolyte solution in lithium metal or anode-free battery packs, combined with lithium difluoro(oxalic acid) borate and lithium tetrafluoroborate, the problem of insufficient circulation performance of the battery pack is solved, and the capacity retention rate is significantly improved. It is suitable for electric vehicles and energy storage systems.

CN113273012BActive Publication Date: 2025-04-25TESLA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080008332.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-08
Filing Date
2020-01-07
Publication Date
2025-04-25
Estimated Expiration
2040-01-07

AI Technical Summary

Technical Problem

The existing lithium metal and anode-free lithium battery pack systems have insufficient circulation performance, resulting in low capacity retention, limiting their wide application in electric vehicles and energy storage systems.

Method used

A double-salt electrolyte solution is used, specifically lithium difluoro(oxalic acid) borate (LiDFOB) and lithium tetrafluoroborate (LiBF4) are used as salt components, and solvents such as fluorovinyl carbonate are added to the battery pack to improve the capacity retention rate of the battery pack.

Benefits of technology

By using a double salt electrolyte solution, the capacity retention rate of lithium metal or anode-free battery packs is significantly improved, reaching at least more than 50% of the electrolyte used alone of LiDFOB or LiBF4, and performs well under different stack pressures and temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113273012B_ABST
    Figure CN113273012B_ABST
Patent Text Reader

Abstract

The present invention provides an electrolyte solution containing lithium difluoro(oxalate)borate and lithium tetrafluoroborate and a solvent component for lithium metal or anode-free rechargeable battery cells, and a method of using the electrolyte solution to improve the capacity retention of the battery cell. A rechargeable battery system comprising a lithium metal or anode-free battery cell and an electrolyte solution containing lithium difluoro(oxalate)borate and lithium tetrafluoroborate and a solvent component is also provided. The system of the present invention exhibits an improved capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a rechargeable battery system, and more particularly, to a method for improving the capacity retention rate of lithium metal and anode-free lithium batteries and an electrolyte solution for the battery system. Background Art

[0002] Rechargeable batteries are integrated components of energy storage systems for electric vehicles and for grid energy storage (e.g., as a backup power source during power outages, as a microgrid component, etc.). Some such rechargeable battery systems include lithium metal and anode-free lithium batteries. Lithium metal and anode-free lithium batteries have certain advantages over traditional lithium-ion batteries because they have higher energy density. Since anode-free batteries lack an anode coating, they are less expensive and easier to assemble. However, the challenges faced by lithium metal and anode-free lithium batteries have hindered their widespread use. Improving certain properties of lithium metal and anode-free battery systems will allow for wider use of the system. For example, the development of electrolyte compositions that allow lithium metal and anode-free lithium batteries to have commercially acceptable cycling performance is critical to the adoption of such battery systems. Prior to the present invention, it was generally believed in the industry that electrolytes containing only lithium difluoro(oxalate)borate ("LiDFOB") salts were most effective in improving the capacity retention of lithium metal and anode-free lithium batteries. See Jurng S, Brown ZL, Kim J, Lucht BL. Effect of electrolyte on the nanostructure of the solid electrolyte interphase (SEI) and performance of lithium metal anodes. Energy and Environmental Science 2018;11(9):2600-2608.

[0003] definition

[0004] A "cell" or "battery cell" generally refers to an electrochemical cell, which is a device capable of generating electrical energy through a chemical reaction or promoting a chemical reaction by introducing electrical energy. A battery may contain one or more cells.

[0005] A "rechargeable battery" generally refers to an electrical battery that can be charged, discharged to a load, and recharged multiple times. In the present disclosure, multiple examples are described based on anode-free lithium-ion batteries. However, embodiments of the present disclosure are not limited to one type of anode-free rechargeable battery and can be implemented in conjunction with various lithium metal or anode-free rechargeable battery technologies. Summary of the invention

[0006] The present invention encompasses methods for improving the capacity retention of an anode-free lithium battery system and electrolyte solutions for the battery system. It has been found that the present methods and electrolyte solutions surprisingly improve the capacity retention of an anode-free battery system. More specifically, the present invention describes that a combination of LiDFOB and lithium tetrafluoroborate ("LiBF4") as a double salt electrolyte in an anode-free battery improves the capacity retention during charge and discharge cycles. It has been found that this double salt electrolyte solution is surprisingly better than the electrolyte using LiDFOB alone or LiBF4 alone. In addition, scanning electron microscopy has shown that the morphology of lithium plating is greatly improved when using double salts compared to that obtained when using conventional electrolytes. Further, when a pouch-type anode-free battery using a double salt electrolyte is subjected to a uniaxial stack pressure in the range of 20 to 500 pounds per square inch, both the charge and discharge capacity retention and the lithium plating morphology are further improved.

[0007] The present invention provides a method for improving the capacity retention rate of lithium metal or anode-free rechargeable battery cells. The method includes providing a salt component comprising lithium difluoro(oxalate)borate and lithium tetrafluoroborate and a solvent component to the battery cell. In one embodiment, the solvent component includes fluoroethylene carbonate. In a further embodiment, a uniaxial stack pressure in the range of 20 to 500 pounds per square inch is applied to the battery cell. In one embodiment, the solvent component includes fluoroethylene carbonate. In a further embodiment, the solvent component further includes diethyl carbonate. In some embodiments, the volume ratio of fluoroethylene carbonate to diethyl carbonate is about 0.5:3 to about 3:0.5. In a further embodiment, the molar concentration of lithium difluoro(oxalate)borate is about 0.5M to 2M, and the molar concentration of lithium tetrafluoroborate is about 0.5M to about 2M. In certain embodiments provided by the present invention, the capacity retention rate of the system is increased by at least 50% compared to a system using only one of lithium difluoro(oxalate)borate or lithium tetrafluoroborate. In further embodiments, the capacity retention of the system is maintained at least 85% over 50 cycles at a charge rate of C / 5 and a discharge rate of C / 2 at 40° C. In other embodiments, the capacity retention of the system is maintained at least 80% over 50 cycles at a charge rate of C / 5 and a discharge rate of C / 2 at 20° C. under a uniaxial stack pressure of at least 150 psi.

[0008] The present invention also provides a rechargeable battery system, which includes a lithium metal or anode-free battery cell and a salt component comprising lithium difluoro (oxalate) borate and lithium tetrafluoroborate and a solvent component. In one embodiment, the solvent component includes fluoroethylene carbonate. In a further embodiment, the solvent component further includes diethyl carbonate. In some embodiments, the volume ratio of fluoroethylene carbonate to diethyl carbonate is from about 0.5:3 to about 3:0.5. In certain embodiments provided by the present invention, the capacity retention rate of the system is increased by at least 50% compared to a system using only one of lithium difluoro (oxalate) borate and lithium tetrafluoroborate. In other embodiments, under a uniaxial stack pressure of at least 150psi, the capacity retention rate of the system is maintained at at least 80% at a charge rate of C / 5 and a discharge rate of C / 2 at 20°C for 50 cycles. In a further embodiment, the system withstands a uniaxial stack pressure of about 20 to about 500psi.

[0009] The present invention also provides a kind of electrolyte composition, it includes the salt component that comprises difluoro (oxalic acid) lithium borate and lithium tetrafluoroborate, and solvent component.In some embodiments, solvent component includes fluoroethylene carbonate.In further embodiment, solvent component further includes diethyl carbonate.In some embodiments, the ratio of fluoroethylene carbonate and diethyl carbonate is about 0.5:3 to about 3:0.5. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Experimental data collected during charge-discharge cycling experiments in anode-free pouch cells at a charge rate of C / 5 and a discharge rate of C / 2 under conditions of a stack pressure of approximately 10 psi, a temperature of 40°C, and a voltage range of 3.6 V to 4.5 V are shown for: 1) 0.6M LiDFOB; 2) 0.6M LiDFOB+0.6M LiBF4; 3) 1.2M LiDFOB; and 4) 1MLiDFOB+0.4M LiBF4.

[0011] Figure 2 Experimental data collected during charge and discharge cycling experiments in anode-free pouch cells at a charge rate of C / 5 and a discharge rate of C / 2 under conditions of a stack pressure of approximately 10 psi, a temperature of 40°C and a voltage range of 3.6 V to 4.5 V are shown: 1) 1MLiBF4; 2) 1M LiPF6; 3) 0.6M LiDFOB; 4) 0.6M LiDFOB+0.6M LiPF6; 5) 0.6M LiDFOB+0.6M LiBF4; and 6) 1.2M LiDFOB.

[0012] Figure 3Experimental data collected during a charge and discharge cycle experiment in an anode-free pouch cell at a charge rate of C / 5 and a discharge rate of C / 2 at a stack pressure of about 10 psi and a temperature of 40°C are shown: 1) 1.2M LiDFOB between a voltage range of 3.6V to 4.2V; 2) 1.2M LiDFOB between a voltage range of 3.6V to 4.3V; 3) 1.2M LiDFOB between a voltage range of 3.6V to 4.5V; 4) 0.6M LiDFOB+0.6M LiBF4 between a voltage range of 3.6V to 4.2V; 5) 0.6M LiDFOB+0.6M LiBF4 between a voltage range of 3.6V to 4.3V; and 6) 0.6M LiDFOB+0.6M LiBF4 between a voltage range of 3.6V to 4.5V.

[0013] Figure 4 Experimental data collected during charge and discharge cycle experiments in an anode-free pouch cell at a charge rate of C / 5 and a discharge rate of C / 2 at a stack pressure of about 10 psi and a temperature of 40°C are shown: 1) 0.6M LiDFOB + 0.6M LiBF4 in a 1:2 volume ratio of ethylene carbonate ("EC"):DEC solvent; 2) 0.6M LiDFOB + 0.6M LiBF4 in a 1:2 volume ratio of FEC:dimethyl carbonate ("DMC") solvent; and 3) 0.6M LiDFOB + 0.6M LiBF4 in a 1:2 volume ratio of FEC:DEC solvent.

[0014] Figure 5 Experimental data collected during charge-discharge cycle experiments in anode-free pouch cells at a charge rate of C / 5 and a discharge rate of C / 2 at a stack pressure of about 10 psi and a temperature of 40°C are shown: 1) 0.6M LiDFOB + 0.6M LiBF4 in a FEC:DMC solvent with a volume ratio of 1:1; and 2) 0.6M LiDFOB + 0.6M LiBF4 in a FEC:DMC solvent with a volume ratio of 1:2.

[0015] Figure 6 Experimental data collected during charge-discharge cycle experiments in anode-free pouch cells at a charge rate of C / 5 and a discharge rate of C / 2 at a stack pressure of about 10 psi and a temperature of 40°C are shown: 1) 1M LiPF6 in a 1:2 volume ratio EC:DEC solution; and 2) 0.6M LiDFOB and 0.6M LiBF4 in a 1:2 volume ratio EC:DEC solution.

[0016] Figure 7The experimental data collected during the charge-discharge cycle experiment at a temperature of 40°C in an anode-free pouch cell at a charge rate of C / 5 and a discharge rate of C / 2 are shown. Figure 8 The SEM images shown are related to: 1) 1M LiPF6 under a cell stack pressure of about 10psi; 2) 1M LiPF6 under a cell stack pressure of about 50psi; 3) 0.6M LiDFOB+0.6M LiBF4 under a cell stack pressure of about 10psi; and 4) 0.6M LiDFOB+0.6M LiBF4 under a cell stack pressure of about 100psi.

[0017] Figure 8 SEM images of the products obtained from the experiments of lithium plating using a Phenom G2-Pro desktop SEM with a 20 μm scale are shown: 1) 1M LiPF6 in a 1:2 volume ratio FEC:DEC solvent under conditions of a stack pressure of about 10 psi and about 50 psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V, after 1 charge and after 50 cycles; and 2) 0.6M LiDFOB and 0.6M LiBF4 in a 1:2 volume ratio FEC:DEC solvent under conditions of a stack pressure of about 10 psi and about 100 psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V, after 1 charge and after 50 cycles. It is worth noting that the plated lithium obtained from the LiDFOB+LiBF4 electrolyte has an extremely small surface area. It is worth noting that the surface area of ​​the plated lithium obtained from the LiDFOB+LiBF4 electrolyte is even smaller under conditions of a stack pressure of 100 psi.

[0018] Fig. 9 The experimental data collected during the charge and discharge cycle experiment in an anode-free pouch cell at a temperature of 20°C with a charge rate of C / 5 and a discharge rate of C / 2, a voltage range of 3.6 to 4.5 V, a uniaxial stack pressure on the electrode of less than 10 psi, a discharge bottom of about 170 psi, and a charge top of about 250 psi are shown. Fig. 9 The significant effect of applied pressure on the cells tested at 20°C using 0.6M LiDFOB+0.6M LiBF4 in FEC:DEC 1:2 is shown. DETAILED DESCRIPTION

[0019] The following description is intended to enable any person skilled in the art to make and use the embodiments, and is provided in the context of a specific application and its requirements. Various modifications to the disclosed embodiments will be apparent to those skilled in the art, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the embodiments shown, but is in the widest scope consistent with the principles and features disclosed herein.

[0020] In one embodiment, an electrolyte composition is provided, comprising a salt component comprising lithium difluoro(oxalate)borate and lithium tetrafluoroborate, and a solvent component. In a further embodiment, the solvent comprises fluoroethylene carbonate. A rechargeable battery system having a battery cell is also provided, the battery cell comprising a salt component comprising lithium difluoro(oxalate)borate and lithium tetrafluoroborate and a solvent component. In a further embodiment, the solvent comprises fluoroethylene carbonate. In some embodiments, the rechargeable battery system comprises an anode-free battery. In other embodiments, the rechargeable battery system comprises a lithium metal anode.

[0021] In a further embodiment, a method for improving the capacity retention of a rechargeable battery cell is provided. The method includes providing a salt component including lithium difluoro(oxalato)borate and lithium tetrafluoroborate and a solvent component to the battery cell.

[0022] In a further embodiment, a rechargeable battery system having an electrolyte of the present invention is subjected to uniaxial stack pressure to improve the morphology of lithium plating and improve capacity retention. In certain embodiments, the uniaxial stack pressure ranges from 10psi to 500psi. In a further embodiment, subjecting the rechargeable battery system to uniaxial stack pressure will significantly improve retention. In a further embodiment, subjecting the rechargeable battery system to uniaxial stack pressure will significantly improve capacity retention, especially at lower temperatures (e.g., 20°C). For example, in some embodiments, subjecting the rechargeable battery system to a higher uniaxial stack pressure (e.g., 170psi) will result in a capacity retention of at least 80% at 20°C and 50 cycles. In some embodiments, the uniaxial stack pressure is at least 50 psi, 60 psi, 70 psi, 80 psi, 90 psi, 100 psi, 110 psi, 120 psi, 130 psi, 140 psi, 150 psi, 160 psi, 170 psi, 180 psi, 190 psi, 200 psi, 210 psi, 220 psi, 230 psi, 240 psi, 250 psi, 260 psi, 270 psi, 280 psi, 400 psi, 410 psi, 420 psi, 430 psi, 440 psi, 450 psi, 460 psi, 470 psi, 480 psi, 490 psi, or 500 psi. In further embodiments, the capacity retention of the system is at least 70%, 75%, 80%, 85%, or 90%.

[0023] In a further embodiment, the solvent component includes fluoroethylene carbonate. According to some embodiments described in the present invention, the solvent component includes fluoroethylene carbonate and an additional solvent. In certain embodiments, the additional solvent is a carbonate solvent. In a further embodiment, the carbonate solvent includes diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, propylene carbonate and a combination thereof. In a further embodiment, wherein fluoroethylene carbonate exists together with an additional carbonate solvent, the volume ratio of fluoroethylene carbonate to the additional carbonate solvent is about 0.5:3 to about 3:0.5. In certain embodiments, the volume ratio of fluoroethylene carbonate to the additional carbonate solvent is about 0.5:3, 0.75:3; 1:3; 1.5:3, 2:3, 2.5:3, 1:1, 1:2, 1:3, 3:0.5, 3:0.75, 3:1, 3:1.5, 3:2, 3:2.5 or 2:1.

[0024] In further embodiments, the molar concentration of lithium difluoro(oxalate)borate in the salt component is between about 0.5 M and 2.0 M. In some embodiments, the molar concentration of lithium difluoro(oxalate)borate in the salt component is about 0.5 M, 0.6 M, 0.7 M, 0.8 M, 0.9 M, 1.0 M, 1.1 M, 1.2 M, 1.3 M, 1.4 M, 1.5 M, 1.6 M, 1.7 M, 1.8 M, 1.9 M, 2.0 M, or 2.1 M.

[0025] In further embodiments, the molar concentration of lithium tetrafluoroborate is between about 0.5M and about 2.0M. In further embodiments, the molar concentration of lithium tetrafluoroborate in the salt component is about 0.5M, 0.6M, 0.7M, 0.8M, 0.9M, 1.0M, 1.1M, 1.2M, 1.3M, 1.4M, 1.5M, 1.6M, 1.7M, 1.8M, 1.9M, 2.0M, 2.1M, 2.3M, 2.4M, 2.5M, 2.6M, 2.7M, 2.8M, 2.9M, 3.0M, 3.1M, 3.2M, 3.3M, 3.4M, 3.5M, 3.6M, 3.7M, 3.8M, 3.9M, 4.0M, 4.1M, 4.2M, 4.3M, 4.4M, 4.5M, 4.6M, 4.7M, 4.8M, 4.9M, or 5.0M.

[0026] According to certain methods described herein, the capacity retention of the battery system described herein is improved by at least 50% compared to a lithium metal-free or anode-free battery system using only one of lithium difluoro(oxalate)borate and lithium tetrafluoroborate. In further embodiments, the capacity retention is improved by at least 55%, 60%, 65%, 70% or 75% compared to a lithium metal-free or anode-free battery system using only one of lithium difluoro(oxalate)borate and lithium tetrafluoroborate.

[0027] In a further embodiment, the capacity retention rate of the battery system is at least 85% after 50 cycles at a charge rate of C / 5 and a discharge rate of C / 2. In a further embodiment, the capacity retention rate is at least 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96% or 97%.

[0028] In further embodiments, the battery systems described herein include any known lithium metal or anode-free lithium battery systems.

[0029] Example

[0030] Dried and sealed single crystal Li[Ni] was obtained from Li-FUN Technology (Xinma Industrial Zone, Jinlong Road, Tianyuan District, Zhuzhou City, Hunan Province, China 412000). 0.5 Mn0.3 Co 0.2 ]O2 (NMC 532) || Copper soft pack battery (260 mAh, 4.5 V). The positive electrode consists of 94 wt.% active material and the single-sided coating active material electrode loading is 16 mg / cm 2 . The positive electrode was compressed to a density of 3.5 g / cm3. The reagents used for the electrolyte included FEC (BASF, purity 99.4%), DEC (BASF, purity >99%), DMC (BASF, purity >99%), LiPF6 (BASF, purity 99.9%), LiDFOB (Capchem or 3M) and LiBF4 (Capchem), and the electrolyte components were mixed using a precision balance in an argon-filled glove box. Before filling with the required electrolyte, the soft-pack battery was cut open and vacuum dried at 100°C for 14 hours to remove any residual moisture. Thereafter, the soft-pack battery was filled with 0.5 mL of electrolyte in an argon-filled glove box and sealed with a bag sealer (MSK-115A vacuum sealer) at a vacuum pressure of -90 kPa (relative to atmospheric pressure). After filling, the battery was kept at 1.5 V for 24 hours to promote wetting and then moved to a temperature box at 40°C for cycling.

[0031] The salt and solvent compositions were tested for their ability to improve capacity retention in these pouch cells.

[0032] Salt composition

[0033] like Figure 1 As shown, the surprising results described in the present invention were observed in charge-discharge cycle experiments using anode-free soft pack batteries, which used: 1) 0.6MLiDFOB; 2) 0.6M LiDFOB+0.6M LiBF4; 3) 1.2MLiDFOB; and 4) 1MLiDFOB+0.4M LiBF4. In the first series of experiments, the tests were conducted at a stack pressure of about 10psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V. The solvent used was a FEC:DEC solvent with a volume ratio of 1:2. The duplicate data points correspond to data from two nominally identical batteries. Figure 1 It is shown that the capacity retention is improved when LiDFOB is used in combination with LiBF4.

[0034] Additional testing confirmed Figure 1The surprising results are shown. Additional cycling experiments were performed in anode-free cells at a charge rate of C / 5 and a discharge rate of C / 2: 1) 1M LiBF4; 2) 1M LiPF6; 3) 0.6M LiDFOB; 4) 0.6M LiDFOB + 0.6M LiPF6; 5) 0.6M LiDFOB + 0.6M LiBF4; and 6) 1.2M LiDFOB. The tests were performed at a stack pressure of about 10 psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V. The solvent used was a FEC:DEC solvent with a volume ratio of 1:2. The duplicate data points correspond to data from two nominally identical cells. Figure 2 It is shown that the capacity retention is improved when LiDFOB is used in combination with LiBF4. Figure 2 It is shown that the combination of LiDFOB and LiPF6 exhibits enhanced capacity retention, although to a lesser extent than when LiDFOB is used in combination with LiBF4. This data suggests that the combination of LiDFOB+LiBF4+LiPF6 may also exhibit advantageous enhanced capacity retention in anode-free cells.

[0035] Upper cut-off voltage test

[0036] The salt compositions were also tested at various upper cutoff voltages to determine whether the surprising results of enhanced capacity retention observed with LiDFOB+LiBF4 were consistent at various voltages. Figure 3 Experimental data collected during charge-discharge cycling experiments at a charge rate of C / 5 and a discharge rate of C / 2 in an anode-free cell are shown: 1) 1.2M LiDFOB in a voltage range of 3.6V to 4.2V; 2) 1.2M LiDFOB in a voltage range of 3.6V to 4.3V; 3) 1.2M LiDFOB in a voltage range of 3.6V to 4.5V; 4) 0.6M LiDFOB+0.6MLiBF4 in a voltage range of 3.6V to 4.2V; 5) 0.6M LiDFOB+0.6M LiBF4 in a voltage range of 3.6V to 4.3V; and 6) 0.6M LiDFOB+0.6M LiBF4 in a voltage range of 3.6V to 4.5V. The tests were conducted at a stack pressure of approximately 10psi and a temperature of 40°C. The duplicate data points correspond to data from two nominally identical cells. The solvent used was FEC:DEC solvent with a volume ratio of 1:2. Figure 3As shown, for different upper cycle voltages (4.2 V, 4.3 V, and 4.5 V), the addition of LiBF4 improves the capacity retention compared to LiDFOB alone. This confirms that LiDFOB+LiBF4 steadily improves the capacity retention at different cycle voltages, while LiDFOB alone performs worse at lower voltages.

[0037] Solvent composition

[0038] Solvent compositions were also tested to determine the effect of solvent on the ability of LiDFOB+LiBF4 to improve the capacity retention of anode-free cells.

[0039] like Figure 4 As shown, during the charge-discharge cycle experiment at a charge rate of C / 5 and a discharge rate of C / 2 in an anode-free battery, the following experimental data were collected: 1) 0.6MLiDFOB+0.6M LiBF4, where the volume ratio of EC:DEC solvent was 1:2; 2) 0.6MLiDFOB+0.6M LiBF4, where the volume ratio of FEC:DMC solvent was 1:2; and 3) 0.6MLiDFOB+0.6MLiBF4, where the volume ratio of FEC:DEC solvent was 1:2. The test was conducted at a cell stack pressure of about 10psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V. The duplicate data points correspond to the data of two nominally identical cells. Figure 4 It was shown that the use of FEC as a solvent in the electrolyte system described in the present invention improves capacity retention, especially when used with other carbonate compounds. Figure 4 It is further shown that using DEC as a co-solvent with FEC shows the greatest improvement in capacity retention.

[0040] Additional experiments were performed to further explore the effect of solvent composition on the enhanced capacity retention of anode-free cells. Figure 5 The experimental data collected during the charge-discharge cycle experiment at a charge rate of C / 5 and a discharge rate of C / 2 in an anode-free cell are shown: 1) 0.6M LiDFOB+0.6M LiBF4, wherein the volume ratio of FEC:DMC solvent is 1:1; and 2) 0.6M LiDFOB+0.6M LiBF4, wherein the volume ratio of FEC:DMC solvent is 1:2. The test was conducted at a cell stack pressure of about 10psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V. Figure 5 It is further shown that changing the FEC:DMC ratio does not significantly affect the capacity retention.

[0041] In addition, we performed additional experiments to evaluate the combination of LiDFOB and LiBF4 in other solvents. Figure 6Experimental data collected during charge-discharge cycling experiments at a charge rate of C / 5 and a discharge rate of C / 2 in an anode-free cell are shown: 1) 1M LiPF6 in a 1:2 volume ratio EC:DEC solvent, and 2) 0.6M LiDFOB and 0.6MLiBF4 in a 1:2 volume ratio EC:DEC solvent. The tests were conducted at a stack pressure of about 10 psi, a temperature of 40°C, and a voltage range of 3.6V to 4.5V. Figure 6 It is further demonstrated that the combination of LiDFOB and LiBF4 also improves the capacity retention in other solvent mixtures.

[0042] Scanning electron microscopy evaluation

[0043] Figure 7 The data collected during the charge-discharge cycle experiment at a charge rate of C / 5 and a discharge rate of C / 2 in an anode-free cell are shown. Figure 8 Experimental data related to the SEM images shown: 1) 1M LiPF6 under a stack pressure of about 10 psi; 2) 1M LiPF6 under a stack pressure of about 50 psi; 3) 0.6M LiDFOB+0.6M LiBF4 under a stack pressure of about 10 psi; and 4) 0.6M LiDFOB+0.6M LiBF4 under a stack pressure of about 100 psi. The solvent used was a FEC:DEC solvent with a volume ratio of 1:2. The samples of the cycling experiment were then examined using a Phenom G2-Pro desktop SEM, where the scale bar is 20 μm: 1) 1M LiPF6 in a 1:2 volume ratio FEC:DEC solvent at a stack pressure of about 10 psi and about 50 psi, a temperature of 40°C, and a voltage range of 3.6 V to 4.5 V, after 1 charge and after 50 cycles; and 2) 0.6M LiDFOB and 0.6M LiBF4 in a 1:2 volume ratio FEC:DEC solvent at a stack pressure of about 10 psi and about 100 psi, a temperature of 40°C, and a voltage range of 3.6 V to 4.5 V, after 1 charge and after 50 cycles. Figure 8 As shown, the 0.6M LiDFOB and 0.6M LiBF4 compositions exhibited much lower surface area lithium deposits than the 1M LiPF6 composition, which is consistent with the improved capacity retention. In addition, the lithium extracted from the cells (0.6M LiDFOB and 0.6M LiBF4) and tested at 100 psi stack pressure exhibited the lowest surface area of ​​all samples tested, consistent with the improved capacity retention. Figure 7The best capacity retention shown is consistent. Without being bound by theory, the inventors believe that applying stack pressure improves the morphology of the lithium by flattening any dendritic deposits that attempt to form. When the salt mixture of the present invention and stack pressure are combined, the lithium morphology obtained is smooth and flat, showing individual particles up to 50 microns in size.

[0044] Tested at 20℃

[0045] Additional tests were performed to evaluate the effect of temperature on the system. The anode-free pouch cell was filled with 0.6MLiDFOB+0.6M LiBF4 in a FEC:DEC 1:2 electrolyte. The cell was tested at 20°C, a voltage range of 3.6V to 4.5V, a charge rate of C / 5, and a discharge rate of C / 2. Two cells were tested with a uniaxial stack pressure of less than 10psi on the electrodes. Two other cells were tested under a uniaxial pressure of about 170psi on the electrode stack at the bottom of the discharge and about 250psi on the top of the charge. Fig. 9 The significant effect of applied pressure on the cell tested at 20°C using 0.6M LiDFOB+0.6M LiBF4 in FEC:DEC 1:2 is shown.

[0046] The foregoing disclosure is not intended to limit the invention to the exact form disclosed or to a specific field of use. Therefore, it should be understood that various alternative embodiments and / or variations of the invention (whether explicitly described or implied herein) are feasible in view of the disclosure of the present invention. Having thus described the embodiments of the present invention, it will be appreciated by those skilled in the art that changes may be made in form and detail without departing from the scope of protection of the present invention. Therefore, the present invention is limited only by the claims. Unless otherwise stated in this specification, the additives mentioned in this specification generally refer to effective additives.

[0047] In the foregoing description, the present invention has been described with reference to specific embodiments. However, as will be appreciated by those skilled in the art, the various embodiments of the present invention may be modified or otherwise implemented in various other ways without departing from the spirit and scope of the present invention. Therefore, the description should be regarded as illustrative and is intended to teach those skilled in the art how to make and use the various embodiments of the disclosed battery system. It should be understood that the forms of the disclosure shown and described herein should be regarded as representative embodiments. Equivalent elements or materials may replace those elements or materials representatively illustrated and described in the present invention. In addition, certain features of the present invention may be used independently of the use of other features, all of which are obvious to those skilled in the art who benefit from the description of the present invention. Expressions used to describe and advocate the present invention, such as "including", "comprising", "combined", "consisting of", "having", "is" are intended to be interpreted in a non-exclusive manner, i.e., allowing items, components or elements that are not explicitly described to also exist. Reference to the singular should also be interpreted as involving the plural. Reference to "about" or "about" should be interpreted as plus or minus 10%.

[0048] In addition, various embodiments disclosed herein should be understood as illustrative and explanatory, and should not be interpreted as limiting the present invention in any way. All combined references (e.g., attaching, pasting, coupling, connecting, etc.) are only used to help readers understand the present invention, and do not constitute limitations, especially the position, direction or use of the system and / or method of the present invention. Therefore, combined references (if any) should be interpreted broadly. In addition, this combined reference does not necessarily mean that two elements are directly connected to each other.

[0049] In addition, all numerical terms, such as but not limited to "first", "second", "third", "primary", "secondary", "primary" or any other general and / or numerical terms, should also be regarded as identifiers merely to assist the reader in understanding the various elements, embodiments, variations and / or improvements of the present invention, and in particular shall not create any limitation on the order or preference of any element, embodiment, variation and / or improvement relative to or over another element, embodiment, variation and / or improvement.

[0050] It should also be understood that one or more of the elements depicted in the illustrations / diagrams may also be implemented in a more separate or integrated manner, or even removed or rendered inoperable in some cases, as may be useful depending on the particular application.

Claims

1. A method for improving the capacity retention of a lithium metal or anode-free rechargeable battery cell, comprising: providing a battery cell with a salt component comprising lithium difluoro(oxalato)borate and lithium tetrafluoroborate, and a solvent component consisting essentially of a first solvent component and a second solvent component, wherein the first solvent component is fluoroethylene carbonate, and the second solvent component is dimethyl carbonate or diethyl carbonate, wherein the molar concentration of lithium difluoro(oxalato)borate is 0.5M to 2M, and the molar concentration of lithium tetrafluoroborate is "0.4M" or "0.5M to 2M", and The volume ratio of the first solvent component to the second solvent component is 1:1 to 1:

2.

2. The method according to claim 1, wherein: A uniaxial stack pressure in the range of 20 to 500 pounds per square inch is applied to the battery cells.

3. The method of claim 1, wherein the second solvent component is dimethyl carbonate.

4. The method of claim 1, wherein the second solvent component is diethyl carbonate. The method according to claim 1 , wherein the volume ratio of the first solvent component to the second solvent component is 1:

1.

6. The method according to claim 1, wherein the molar concentration of lithium difluoro(oxalato)borate is 0.6M to 1M.

7. The method according to claim 1, wherein the molar concentration of lithium tetrafluoroborate is "0.4M" or "0.5M to 0.6M".

8. The method of claim 1, wherein the capacity retention of the battery cell is improved by at least 50% compared to a battery cell using only one of lithium difluoro(oxalato)borate and lithium tetrafluoroborate.

9. The method according to claim 1, wherein: The capacity retention of the battery cell is maintained at least 85% over 50 cycles at 40° C. at a charge rate of C / 5 and a discharge rate of C / 2.

10. The method according to claim 1, wherein: The battery cell has a capacity retention of at least 80% at a charge rate of C / 5 and a discharge rate of C / 2 over 50 cycles at 20°C under a uniaxial stack pressure of at least 150 psi.

11. A rechargeable battery system including a lithium metal or anode-free battery cell, comprising: A salt component comprising lithium difluoro(oxalato)borate and lithium tetrafluoroborate, and a solvent component; and The solvent component consists essentially of a first solvent component and a second solvent component, wherein the first solvent component is fluoroethylene carbonate, and the second solvent component is dimethyl carbonate or diethyl carbonate, wherein the molar concentration of lithium difluoro(oxalato)borate is 0.5M to 1M, and the molar concentration of lithium tetrafluoroborate is "0.4M" or "0.5M to 0.6M", and The volume ratio of the first solvent component to the second solvent component is 0.5:3 to 3:0.

5.

12. The rechargeable battery system according to claim 11, wherein: The second solvent component is dimethyl carbonate.

13. The rechargeable battery system according to claim 11, wherein: The second solvent component is diethyl carbonate.

14. The rechargeable battery system according to claim 11, wherein: The volume ratio of the first solvent component to the second solvent component is 1:1 to 1:

2.

15. The rechargeable battery system according to claim 11, wherein: Compared with a system using only one of lithium difluoro(oxalato)borate and lithium tetrafluoroborate, the capacity retention of the system is improved by at least 50%.

16. The rechargeable battery system according to claim 11, wherein: When the system is subjected to a uniaxial stack pressure of at least 150 psi, the capacity retention of the system is maintained at least 80% over 50 cycles at 20°C with a charge rate of C / 5 and a discharge rate of C / 2.

17. The rechargeable battery system according to claim 11, wherein: The system was subjected to uniaxial stack pressures ranging from 20 to 500 psi.

18. An electrolyte composition comprising a salt component comprising lithium difluoro(oxalato)borate and lithium tetrafluoroborate, and a solvent component consisting essentially of a first solvent component and a second solvent component, wherein the first solvent component is fluoroethylene carbonate, and the second solvent component is dimethyl carbonate or diethyl carbonate, wherein the molar concentration of lithium difluoro(oxalato)borate is 0.5M to 1M, and the molar concentration of lithium tetrafluoroborate is "0.4M" or "0.5M to 0.6M", and The volume ratio of the first solvent component to the second solvent component is 1:1 to 1:

2.

19. The composition of claim 18, wherein the second solvent component is dimethyl carbonate.

20. The composition of claim 18, wherein the second solvent component is diethyl carbonate.

21. The method of claim 1, wherein the volume ratio of the first solvent component to the second solvent component is 1:

2.

22. The method of claim 6, wherein the second solvent component is diethyl carbonate, and wherein the volume ratio of fluoroethylene carbonate to diethyl carbonate is 1:

2.

23. The method of claim 7, wherein the molar concentration of lithium tetrafluoroborate is 0.5 M to 0.6 M, and wherein the second solvent component is dimethyl carbonate.

Citation Information

Patent Citations

  • High-voltage electrolyte for lithium ion battery

    CN104934638A

  • Nonaqueous electrolytic solution and nonaqueous-electrolyte battery employing the same

    US20120219866A1

  • Thermal management system and method for a solid-state energy storing device

    US6087036A